Materials science and technology : a comprehensive treatment. Volume 18, Processing of polymers / edited by R.W. Cahn, P. Haasen, E.J. Kramer; Vol. editor : Han E. H. Meijer - Meijer, Han E. H.
Vol. 18 Processing of polymers in 1997